2018
DOI: 10.15296/ijwhr.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Management of Early Menopause Using Traditional Persian Medicine: A Case Report

Abstract: Interruption of the activity of ovary before the age of forty is called premature ovarian failure (POF) in which ovaries lose their follicular and hormonal functions. A decline in the number of ovules before the age of menopause is a physiologic phenomenon. In the present case report, treatment of a patient by POF was reported using traditional Persian medicine principles. In Persian medicine, each humor has its own temperament. A change in the temperament and quality or quantity of these humors causes the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Almost 85% of PID cases are among the typical infections in sexually active women of reproductive age whereas the other 15% of infections follow the procedures that break the cervical mucus barrier. Insertion of intrauterine devices, uterine curettage, hysteroscopy, endometrial biopsy, and hysterosalpingography are several examples of these procedures (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 85% of PID cases are among the typical infections in sexually active women of reproductive age whereas the other 15% of infections follow the procedures that break the cervical mucus barrier. Insertion of intrauterine devices, uterine curettage, hysteroscopy, endometrial biopsy, and hysterosalpingography are several examples of these procedures (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of a large-scale study on 12 285 couples in 30 provinces in 2008, the prevalence of infertility was reported 8% in Iran (10). Further, the findings of another study conducted in Iran showed the prevalence of infertility was 2.5% and the national study 401 estimated the prevalence of primary infertility by 1.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in another similar study, primary and secondary infertility were estimated to be 1.7% and 10.5%, respectively. Nowadays, many infertile couples (40-50%) have the chance of pregnancy with the advent of science and the use of modern methods of infertility treatment (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of infertility could be a male or female factor or a mixed factor. About 2, 40, and 2% of infertility problems are related to a male, female, and mixed factor, respectively (1)(2)(3). The most common female cause is ovulatory disorders (40-35%).…”
Section: Introductionmentioning
confidence: 99%